Social Media Entertainment Among Children in Tema, Ghana: Impact of Restrictions and Associated Factors - Sylvester Kyei-Gyamfi; Frank Kyei-Arthur (International Journal of Pediatrics)
Conclusion: This study demonstrates that most children use social media for entertainment, and limiting children’s access to social media may lead to information isolation, entertainment deficit, and digital disengagement. Consequently, stakeholders must devise interventions that enhance children’s access and responsible use of social media for entertainment. Future studies should examine children’s frequency and intensity of social media use and its potential benefits and associated risks.